POLITE EXPRESSIONS USED BY TEACHERS IN TEACHING ENGLISH IN THE CLASSROOM - Rauf, Masykur (Elite : English and Literature Journal, 2017)
Abstract The objectives of this research were to find out the kinds of polite expressions used by teachers in teaching English in the classroom and effects of polite expressions used by teachers to students. The researcher applied descriptive qualitative research and used purposive sampling in getting the data. The subject of this research was one English teacher of SMP 24 Makassar. The researcher did classroom observation by recording the teacher’s activities and analyzed it through Brown and Levinson’s theory of politeness strategies. The researcher found that some polite expressions of strategies that the teacher used is divided into two types. First, Positive Politeness (PP) such as greetings, notice and attend the hearer, exaggerate, intensify interest of hearer, use in-group identity makers, seeking agreement, presuppose/ raise/ assert common ground, include both speaker and hearer in the activity, giving or asking reasons, assume or assert reciprocity and giving gifts to hearer (goods, sympathy); and Negative Politeness (NP) such as Being conventionally indirect, Questions, Minimize the imposition, Giving deference, Apologize, Nominalize. The effects to students are: being motivated in their study, student’s attitude (affective), respect to teacher, self-confidence, being active and attending in teaching learning process, and honest. Abstrak Ekspresi Kesopanan yang Digunakan oleh Guru dalam Mengajar Bahasa Inggris di Kelas. Tujuan dari penelitian ini adalah untuk mengetahui jenis ekspresi kesopanan yang digunakan oleh guru dalam mengajar bahasa Inggris di kelas dan efek dari ekspresi kesopanan yang digunakan oleh guru kepada siswa. Ini adalah penelitian deskriptif kualitatif yang menggunakan purposive sampling untuk mendapatkan data. Subjek penelitian ini adalah salah seorang guru Bahasa Inggris SMP 24 Makassar. Peneliti melakukan observasi kelas dengan merekam aktivitas guru dan dianalisis meggunakan teori strategi kesantunan Brown dan Levinson. Peneliti menemukan bahwa ekspresi kesopanan yang digunakan guru dibagi menjadi dua jenis. Pertama, Kesopanan Positif (KP) seperti salam, pemberitahuan dan menyapa pendengar, membesar-besarkan, mengintensifkan kepentingan pendengar, gunakan pembuat identitas dalam kelompok, mencari kesepakatan, mengandaikan / angkat / menegaskan, mengikutsertakan pembicara dan pendengar dalam kegiatan, memberi atau meminta alasan, mengasumsikan atau menegaskan timbal balik dan memberikan hadiah kepada pendengar (barang, simpati); dan kesopanan negatif (np) seperti menjadi konvensional tidak langsung, pertanyaan, minimalkan pembebanan, memberikan rasa hormat, minta maaf, nominalize. Efek untuk siswa: termotivasi dalam pelajaran mereka, sikap siswa (afektif), sehubungan dengan guru, kepercayaan diri, aktif dan menghadiri proses belajar mengajar, serta jujur.